1984
DOI: 10.1126/science.6424234
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Rearranged μ Gene and Translocated c- myc in Mouse 3T3 Cells × Burkitt Lymphoma Cell Hybrids

Abstract: The productively rearranged immunoglobulin mu chain gene and the translocated cellular oncogene c-myc are transcribed at high levels both in human Burkitt lymphoma cells carrying the t(8;14) chromosome translocation and in mouse plasmacytoma X Burkitt lymphoma cell hybrids. In the experiments reported here these genes were found to be repressed in mouse 3T3 fibroblast X Burkitt lymphoma cell hybrids. Such repression probably occurs at the transcriptional level since no human mu- and c-myc messenger RNA's are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 20 publications
3
29
0
Order By: Relevance
“…The inserted sequence shows 62% homology to a region of the Kpn I element beginning approximately 900 bp from the 3' end of the Kpn I element. This is similar to the homology between mouse MIF repetitive element and monkey Kpn I element (39). It is of interest that the homology is in the 3' to 5' orientation of the Kpn I element, suggesting a possibility of inversion of the inserted element.…”
Section: Methodssupporting
confidence: 49%
“…The inserted sequence shows 62% homology to a region of the Kpn I element beginning approximately 900 bp from the 3' end of the Kpn I element. This is similar to the homology between mouse MIF repetitive element and monkey Kpn I element (39). It is of interest that the homology is in the 3' to 5' orientation of the Kpn I element, suggesting a possibility of inversion of the inserted element.…”
Section: Methodssupporting
confidence: 49%
“…However, it is likely that sequences in the immunoglobulin loci to which the c-myc gene is translocated also play a role in c-myc activation. Cell hybrid studies have shown that the translocated c-myc gene is activated only in the B-cell background (36). In rare instances of Burkitt lymphoma (37) and murine plasmacytoma (38), the c-myc gene translocates to the immunoglobulin Ig heavy chain enhancer sequence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, somatic cell hybrid studies demonstrate that the cryptic promoters of truncated c-myc genes adjacent to immunoglobulin switch, and constant regions are active, in a B-cell background but not in lymphoblastoid or nonlymphoid cell backgrounds (10,31,32). This demonstrates a requirement for B-cell-specific factors and suggests that B-cell factors normally involved in immunoglobulin gene transcription may also activate the cryptic c-myc promoters translocated adjacent to immunoglobulin genes.…”
mentioning
confidence: 92%
“…6,1986 on May 10, 2018 by guest http://mcb.asm.org/ Downloaded from did not cause the altered chromatin structure since the reciprocally translocated 5' c-myc region did not acquire the same structure. Furthermore, since activation of translocated c-myc genes requires a mature B-cell environment (10,31,32), adjacent Ca sequences are causally implicated in this altered chromatin structure.…”
mentioning
confidence: 99%